HUBUNGAN TINGKAT KEPATUHAN PELAKSANAAN PROTAP PERAWATAN LUKA DENGAN KEJADIAN INFEKSI LUKA POST SECTIO CAESAREA (SC) DI RUANG MAWAR I RSUD DR. MOEWARDI SURAKARTA - Himatusujanah Himatusujanah; Faizah Bety Rahayuningsih (Universitas Muhammadiyah Surakarta, 2008)
Backgraund: Indonesian country have the most negatif dateless accidently, special to infection of wound patient post section caesarea. At Cipto Mangunkusumo Jakarta hospital in 1990 year be present dateless infection of wound 12% is unadulterated surgical operation and contamination. Dr Sardjito hospital infection of wound 15%, dr Soetomo Surabaya hospital hospital infection of wound 20%. Dr Moewardi Surakarta hospital infection of wound 13%. Underlying Theory: Section caesarea is fetus be born used slice on partition stomach and partition of womb. Wound of treatment is efforts to clean, medication and shut up using sterile technique. Methode: This my research using cross-sectional method,using chi value is 5% and df value is 2. Research Result: Result are significant (p) value is 0.001 < 0.05 can be to talk Ho to depart. Degree of obedient implementation permanent wound programme with infection of wound patient post section caesarea in Mawar I room Moewardi Surakarta hospital is to be connected. Conclusion: Result are obedient degree implementation permanent programme is good that is 26 (60.5%),less that is 8 (18.6%) and infection accidently that is 9 (20.9%). Suggestion: Dear university student, if you are interest to be research this topic be obtained more than sample